21ST CENTURY SKILLS AND METHODS FOR THEIR SELF-FORMATION - Abdullayev Abduvohid Alisher ugli (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: The concept of 21st century skills has become one of the most widely referenced frameworks in contemporary educational policy and practice, yet substantial ambiguity persists regarding its theoretical foundations, empirical operationalisation, and the specific pedagogical methods most effective for self-directed skill formation. This article synthesises the major theoretical frameworks defining 21st century skills, examines the empirical evidence for the effectiveness of self-formation strategies, and proposes an integrated methodological model for skill development oriented toward autonomy, metacognition, and lifelong learning.